The state of COVID-19 contact tracing following relaxation of the national lockdown: A qualitative study among surveillance response teams in Kampala, Uganda - Andrew Kuguminkiriza Tusubira; Steven Ssendagire; Angela Nakanwagi Kisakye; Elizabeth Muhumuza; Dorothy Akong; Winnie Agwang; David Kansiime; Stella Martha Migamba; Doreen Tuhebwe; Elizabeth Ekirapa Kiracho (Journal of Interventional Epidemiology and Public Health)
Introduction: The surge in COVID-19 cases triggered a need for surveillance systems to implement new strategies that augment and accelerate manual contact tracing. In Uganda, COVID-19 cases increased exponentially following the relaxation of the national lockdown. However, little is known about how the surveillance system mitigated COVID-19 transmission during this period. We sought to understand how contact tracing was being conducted in Kampala district following relaxation of the national lockdown.